Pre-trained POS tagging models for German social media - Rehbein, Ines; Ruppenhofer, Josef; Zimmermann, Victor (Universität, 2020)
Pre-trained POS tagging models for the HunPos tagger (Halácsy et al. 2007) the biLSTM-char-CRF tagger (Reimers & Gurevych 2017) Online-Flors (Yin ...